"Garugiwa In Line" A Portrait of The Success of Local Wisdom-Based Population Administration Service Innovation in Ende District - Indriyati Indriyati; Yohanes K. Ethelbert; Boni Saputra (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
This research study aims to see the success of the "Garugiwa In Line" innovation in population administration services. The invention, which adopts the name of the GARUGIWA bird or Arwah Bird, which is an endemic bird that only lives in the Kelimutu mountains in Ende Regency, has recorded various performance achievements in population administration services (Adminduk) for the people of Ende Regency. This research method uses a descriptive qualitative approach. It examines the research focus by measuring government innovation strategies using indicators of integrated services, utilization of cooperation, citizen involvement, and utilization of communication and information technology. The results showed that from the percentage achievement of national service indicators, Disdukcapil Kab. Ende can increase the percentage achievement of service indicators every year. This describes that aspects of local wisdom can be "energy" that contributes to the performance of public services.